Redescriptions of Green’s three species of Ceronema Maskell (Hemiptera: Coccomorpha: Coccidae) from Sri Lanka and their placement in two new genera - Hodgson, Chris J. (Zootaxa, 2026)
In the early part of the last century, Green described three species of soft scale insect (Hemiptera: Coccomorpha: Coccidae) in the genus Ceronema Maskell from Sri Lanka; these species have not been studied since. Ceronema is currently being revised and the three species from Sri Lanka clearly are not congeneric with the type species of the genus, C. banksiae Maskell, which is restricted to Australia. The three Sri Lankan species, namely Ceronema iceryoides Green, C. fryeri Green and C. koebeli Green, are here redescribed, illustrated and placed in two new genera as follows: C. iceryoides and C. koebeli are placed in Sinhalacoccus Hodgson, gen. nov. as Sinhalacoccus iceryoides (Green) comb. nov. and Si. koebeli (Green) comb. nov. respectively, and C. fryeri is placed in Serendipicoccus Hodgson, gen. nov. as Serendipicoccus fryeri (Green) comb. nov. The morphology of the adult females of these two genera is compared with that of Ceronema and a key is presented for the separation of these three genera from other possibly related genera.